New data on the taxonomy and distribution of ten Neotropical chewing lice of the genus Myrsidea (Phthiraptera: Menoponidae), including the description of a new species - Kolencik, Stanislav; Sychra, Oldrich; Valan, Miroslav; Literak, Ivan (Zootaxa, 2016)
The new species Myrsidea alexanderi is described and illustrated ex Pheugopedius maculipectus (Troglodytidae) from Honduras. Redescriptions and illustrations are given for both sexes of Myrsidea chiapensis ex Calocitta formosa from Costa Rica, and the male of M. dissimilis ex Progne chalybea from Brazil. Also, seven other previously known species or subspecies of the louse genus Myrsidea are recorded and discussed from passerine birds of the Neotropical Region, as follows: Myrsidea antiqua, Myrsidea balteri, Myrsidea diffusa, Myrsidea nesomimi borealis, Myrsidea paleno, Myrsidea psittaci and Myrsidea serini. Our data increase knowledge of intraspecific morphological variability within these species, and also of their host and geographical distribution. New host-louse associations are: Agelaioides badius for M. psittaci; Basileuterus culicivorus and Myiothlypis leucoblephara for M. paleno; Mimus saturninus for M. nesomimi borealis; and Icterus dominicensis and Molothrus rufoaxillaris for Myrsidea sp.
Keywords: Animals; velikost těla; Kostarika; Female; Honduras; Amblycera; ženské pohlaví; Organ Size; Brazil; Passeriformes; anatomické struktury zvířat; Body Size; nemoci ptáků; zavšivení; Animal Distribution; Lice Infestations; Bird Diseases; Animal Structures; velikost orgánu; Male; Costa Rica; Brazílie; ekosystém; Ecosystem; zvířata; mužské pohlaví; rozšíření zvířat